Characteristics and Clinical Significance of Intestinal Microbiota in Patients with Chronic Hepatitis B Cirrhosis and Type 2 Diabetes Mellitus - Xiu Sun; Xin Chi; Yingying Zhao; Shunai Liu; Huichun Xing (Journal of Diabetes Research)
Background. Chronic hepatitis B cirrhosis is often accompanied by glucose metabolism disorder, and intestinal microbiota was closely related to both cirrhosis and diabetes. There are few studies on the role of intestinal microbiota in hepatitis B liver cirrhosis and diabetes mellitus (LCDM). The purpose of this study was to investigate the characteristics of intestinal microbiota in patients with LCDM and to evaluate the relationship between the severity of intestinal microbiota imbalance and clinical significance. Methods. A case-controlled study was conducted. People who met the inclusion and exclusion criteria of chronic HBV-related liver cirrhosis (LC), LCDM, and healthy controls (HC) were enrolled in, and their fecal and blood samples were collected. The V3-V4 region of 16s rDNA gene of fecal microbiota was sequenced; the bioinformatics analysis including α-diversity, β-diversity, and linear discriminant analysis (LDA) effect size (LEfSe) was performed; and the correlation between bacteria and clinical indexes was analyzed. Results. A total of 70 participants completed fecal and blood tests, including 20 HC, 20 LCDM, and 30 LC. The α diversity of intestinal microbiota in the LCDM decreased than that in the HC. The abundance of Proteobacteria, Streptococcus, Escherichia-Shigella, and Lactobacillus increased, while the abundance of Bacteroidota, Bacteroides, Prevotella, Faecalibacterium, and Lachnospira decreased in the LCDM compared with the HC. The abundance of Lactobacillus, Roseburia, and Veillonella and the degree of hepatitis B cirrhosis dysbiosis indicator (HBCDI) increased in the LCDM than in the LC. The abundance of Escherichia-Shigella, Veillonella, and Lactobacillus positively correlated with liver injury and fasting blood glucose (FBG) level. The abundance of Escherichia-Shigella, Veillonella, Streptococcus, and Lactobacillus increased more significantly when FBG and glycosylated hemoglobin level increased. Conclusion. Intestinal microbiota of patients with LCDM was significantly disordered, and the degree was more serious than that cirrhosis patients without diabetes.